An Analysis of Metaphor for Corona on Headlines News - Nur Lailatul Aqromi (Pioneer: Journal of Language and Literature, 2020)
This paper examines, describes, and analyzes the types of metaphor used in Tribunnews.com headlines particularly Corona issues. The data were taken from March 2nd 2020 until July 14th 2020 with keywords Corona and Covid-19 and, were analyzed in the frame of qualitative method. The data taken were analyzed by using conceptual metaphor proposed by Lakof and Johnson. The analysis deals with the types of metaphor called structural metaphor, ontological metaphor, and orientational metaphor. The result shows how Corona was mapped into other domain in order to simplify and attract reader’s attention.